Prinsip-Prinsip Kesantunan Berbahasa dalam Fitur Chat di Aplikasi Ojek Online - Syarah Amaliyah Usman; M. Oky Fardian Gafari (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
The explanation and description of the deviations and the application of the Leech principle of chaos in the Gojek, Grab, and inDriver application char features are the objectives of this study. The theory used in this study using the theory of Leech language chaos principles. This research data is a matching of online scooter drivers and consumers in chat features in online scout apps, through recording, crawling, and observation. The data source obtained is ten data in each online application. (Gojek, Grab, inDriver). The instrumental indicator used consists of the principle of excellence that encompasses the maximum of wisdom, charity, appreciation, humility, agreement, and sympathy. The data collection technique used is observation and recording. Data analysis techniques used are, observing and observing, recording, collecting data, and analyzing data. The results of the research show that the most common form of deviation is the maxima of intelligence in which drivers and customers do not want to reduce the loss to themselves and increase the benefit of others. Meanwhile, the dominant form of application of the principle is the maximum intelligence demonstrated through agreement and sympathy.